Interdisciplinary Research: A Phenomenological Perspective on Participation - Niclas Ekberg; Cecilia Ferm Almqvist (Journal of Interdisciplinary Sciences)
To advance the efficiency and effectiveness of inter-disciplinary research, and to obtain valid strategies for inter-disciplinary projects, there is a need to define inter-disciplinary research approaches explicitly. The current study aims generally to further the understanding of interdisciplinary ways of conducting research, and specifically to describe and explore the challenges and opportunities that characterize research projects which move across borders of different research areas as well as the various disciplinary homes of the collaborating researchers in a recently performed project focusing on Bildung and streamed art. Written reflections from the six participants in the project, representing the disciplines of music education, musicology, education, English literature, sound engineering as well as media and technology science was analyzed and interpreted in relation to Alfred Schütz’ theory of phenomenological sociology. The results are presented through six themes, which together fulfill the aim of the study; (i) Crossed borders, perspectives, and contexts, (ii) Common concepts, definitions, and reconstructions, (iii) Status of theory and explorative freedom, (iv) State of the art and innovative potential, (v) Scientific identity and positioning work (vi) Place, activity, and performance.